Kajian Mutu Ikan Kayu Serut Yang Dikemas Plastik Dengan Nitrogen Dan Tanpa Nitrogen - Sitepu, Agape Isak; Reo, Albert Royke; Makapedua, Daisy Monica; Lohoo, Helen Jenny; Kaseger, Bertie Elias; Dotulong, Verly; Damongilala, Lena Jeane (Sam Ratulangi University, 2021)
Skipjack (Katsuwonuspelamis L) is classified as a pelagic fish, and one of the fishery resources export commodity. Skipjack is found in almost all Indonesian waters, especially in North Sulawesi. Katsuobushi has a relatively long product durability compared to the fish preservation with other methods such as cakalang fufu fish preservation. The purpose of this study is to determine and study the quality and shelf life of Hanakatsuo that was packed plastic with nitrogen and without nitrogen. Hanakatsuo was stored in ambient temperature for 0, 7 and 14 days in order to evaluate the quality of product during storage. The method used in this research was organoleptic test, water content and Total Place Count (TPC). The result of organoleptic test for appearance, odor and texture was an average of 7 which comply the Indonesia national standart (SNI). The result of moisture content of hanakatsuo that packed with nitrogen during the storage period for 0, 7 and 14 days showed increasing of water content according to the storage period experienced an increase in water content, The water content of hanakatsuo which packed without nitrogen increased during the storage period of 0 and 7 days while on the storage of 14 days decreased to 16,45% but still comply to the SNI. Based on the TPC test showed that hanakatsuo that packed in plastic without nitrogen do not comply the SNI, while hanakatsuo that packed with nitrogen on days 0 and 7 comply the SNI. Ikan cakalang (Katsuwonus pelamis L) tergolong sumber daya perikanan pelagis, dan merupakan salah satu komoditi ekspor. Ikan cakalang terdapat hampir di seluruh perairan Indonesia, terutama di Sulawesi Utara. Ikan kayu memiliki daya awet produk yang tergolong lama dibandingkan dengan pengawetan ikan dengan metode lainnya seperti pengawetan ikan cakalang fufu. Tujuan penelitian ini untuk mengetahui dan mempelajari mutu dan masa simpan ikan kayu serut yang dikemas plastik dengan nitrogen dan tanpa nitrogen. Metode yang dilakukan untuk uji organoleptik, kadar air dan uji Angka Lempeng Total (ALT) dengan perlakuan penyimpanan 0 hari, 7 hari dan 14 hari. Berdasarkan hasil pengujian organoleptik kenampakan, bau dan tekstur dengan rata-rata 7 memenuhi SNI. Berdasarkan hasil uji kadar air penyimpanan hari ke 0, 7 dan 14 hari mengalami kenaikan kadar air sedangkan pada produk ikan kayu serut yang dikemas plastik tanpa nitrogen mengalami kenaikan kadar air pada penyimpanan hari ke 0, 7 dan mengalami penurunan kadar air pada hari ke 14 dengan nilai tertinggi 16.45 memenuhi SNI. Berdasarkan hasil uji ALT pada produk ikan kayu serut yang dikemas plastik tanpa nitrogen tidak memenuhi Standar SNI, sedangkan pada produk ikan kayu serut yang dikemas plastik dengan nitrogen pada hari ke 0 dan 7 memenuhi standar SNI.